MIND MAPPING MENINGKATKAN MOTIVASI BELAJAR IPS - Sunarti; Purnaminingsih, Wahyu (Program Magister Pendidikan IPS UPY, 2024)
This study aims to find out how the application of the mind mapping method can increase social studies learning motivation in class VIIIA students of SMPN 2 Saptosari Gunungkidul in the 2021/2022 academic year. This type of research is Classroom Action Research with two cycles, each cycle consisting of planning, action, observation and reflection. The subjects of this study were students of class VIIIA SMPN 2 Saptosari with a total of 25 students consisting of 11 girls and 14 boys. The data analysis technique in this study used quantitative descriptive analysis. The results of the study indicate that the mind mapping method in learning can increase the motivation to learn social studies. Social studies learning motivation in pre-cycle is 40%, in Cycle I it increases to 52%, and in Cycle II it increases to 80%. It can be concluded that the application of the mind mapping method in social studies learning can increase learning motivation.